2021
DOI: 10.1039/d1nj02684d
|View full text |Cite
|
Sign up to set email alerts
|

Anion recognition by anthracene appended ortho-aminomethylphenylboronic acid: a new PET-based sensing mechanism

Abstract: Interactions of anthracene appended ortho-aminomethylphenylboronic acid 1 with 20 organic and inorganic anions have been studied by fluorescence, 1H and 11B NMR titrations in DMSO. Carboxylate, phosphate and sulphate anions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…1(a)) and its derivatives are widely used pH probes with the fluorescence off-on response based on the PET process from the secondary amine to the anthracene unit. [23][24][25][26][27] When the secondary amine group with lone pair electrons binds a proton, the PET process is prohibited, and the fluorescence intensity increases. [23][24][25][26][27] An amino-substituted rhodamine derivative, aminorhodamine (ARh), shows a similar fluorescence off-on pH response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)) and its derivatives are widely used pH probes with the fluorescence off-on response based on the PET process from the secondary amine to the anthracene unit. [23][24][25][26][27] When the secondary amine group with lone pair electrons binds a proton, the PET process is prohibited, and the fluorescence intensity increases. [23][24][25][26][27] An amino-substituted rhodamine derivative, aminorhodamine (ARh), shows a similar fluorescence off-on pH response.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] When the secondary amine group with lone pair electrons binds a proton, the PET process is prohibited, and the fluorescence intensity increases. [23][24][25][26][27] An amino-substituted rhodamine derivative, aminorhodamine (ARh), shows a similar fluorescence off-on pH response. The fluorescence quenching of ARh has previously been explained using a twisted intramolecular charge transfer (TICT) model in the studies of Plaza and Martin.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Yatsimirsky et al have reported that AnBOH shows the signal for the hydroxyl protons of the B(OH) 2 moiety in the intramolecular OH⋯N hydrogen bonding even in a polar solvent such as DMSO- d 6 , leading to the suppression of the PET. 19 The fact also suggested the existence of TF-2H in THF- d 8 without the addition of water. The addition of water to the THF- d 8 solution of TF-2 induces shifts of the signals for the aliphatic and aromatic protons and the disappearance of the signal for the B(OH) 2 protons toward producing TF-2W or TF-2WH , as with the case of TF-2 in acetonitrile- d 3 .…”
Section: Resultsmentioning
confidence: 97%
“…Both types of anion recognitions are important for sensing and other applications. The majority of reported boronic acid-based anion sensors operate via the coordinate bonding and are designed for detection of fluoride, but recently, the hydrogen bonding mode is also exploited in the design of anion receptors . The type of anion binding is essential for applications of boronic acids in catalysis, and it is also the subject of computational analysis .…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, at least two aspects in which boronic acids differ significantly from other OH donor receptors. First, acyclic alcohol or phenol-based receptors bind anions only in low polar media with MeCN being the most polar solvent where the binding is still detectable, while boronic acids successfully operate even in DMSO. , Second, boronic acids have an additional Lewis acid binding site, which gives them more options for anion recognition. In particular, in water, where the hydrogen bonding becomes inefficient, boronic acids still can bind anions due to their Lewis acidity .…”
Section: Introductionmentioning
confidence: 99%